2022
DOI: 10.12688/hrbopenres.13534.2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the COVID-19 pandemic on prehospital emergency care for adults with stroke and transient ischaemic attack: A protocol for a systematic review and meta-analysis

Abstract: Background: The COVID-19 pandemic impacted on health service provision worldwide, including care for acute time sensitive conditions. Stroke and transient ischaemic attacks (TIA) are particularly vulnerable to pressures on healthcare delivery as they require immediate diagnosis and treatment. The global impact of the COVID-19 pandemic on prehospital emergency care for stroke/TIA is still largely unknown. Thus, the aim of this study is to conduct a systematic review and meta-analysis to investigate the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In the study conducted by Burton et al, the time spent in EMS was found to be approximately 26.5 minutes (13). In the study conducted by Vuorinen et al, the time spent in EMS was found to be 99 minutes (14).…”
Section: Discussionmentioning
confidence: 95%
“…In the study conducted by Burton et al, the time spent in EMS was found to be approximately 26.5 minutes (13). In the study conducted by Vuorinen et al, the time spent in EMS was found to be 99 minutes (14).…”
Section: Discussionmentioning
confidence: 95%
“…Due to the time-sensitivity of acute stroke/TIA management and treatment any delay in the stroke chain of survival could lead to worse clinical and functional outcomes. Other studies have also reported changes in demographic characteristics of those presenting with stroke/TIA during the COVID-19 pandemic,62 85 86 whereas further studies found no change in demographics, between the two periods 57 67 87…”
Section: Discussionmentioning
confidence: 97%
“…Whereas other international studies found an increase in suspected stroke/TIA call volume during the period 65 66. At the time of writing, literature in acute stroke care during the COVID-19 pandemic was primarily focused on single centre studies set in hospitals, with a lack of papers focusing on the prehospital response 67. Available prehospital papers focus on either one or more early waves of the COVID-19 pandemic,62 67 and do not investigate emerging patterns over multiple waves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations